MANAJEMEN PENDIDIKAN DINIYAH FORMAL - dewi, ratna; Limbong, Jetro (Perkumpulan Sarjana Manajemen Pendidikan Islam Indonesia, 2018)
This study aims to uncover the situation and conditions for the implementation of Pendidikan Diniyah Formal (PDF) or Formal Religious Education (PRE) management, especially in West Java, as the epicenter of Indonesian Islamic education. However, every year there are students who resign from PDF, which is basically unusual for students studying in formal education. This study uses a qualitative method. Data was collected through interview, document studies and observations. The study was carried out in PRE Al-Jawahir and Al-Masturiyah. The results of the study show that the PRE, besides being held by madrassas (Islamic formal education), can also be organized by pesantren (non-formal Islamic boarding schools). In fact, they got two proofs of graduating formal education in the form of a Wathani Certificate that is equivalent to a National Examination Result Certificate (NERC), and a diploma (graduation certificate). Both proofs of graduation were signed by the head of the PRE and the head of the boarding school. Santri (student) PRE Wushto learns face-to-face in class as much as 52 lessons each week with an allocation of 40 minutes lesson time. Santri PRE Ulya as many as 53 hours, with an allocation of 45 minutes/lesson hours. Face-to-face learning is outside the campus activities such as the traditional text book study, tahfidz al Qur'an and extracurricular activities.